2005
DOI: 10.1007/s11171-005-0053-1
|View full text |Cite
|
Sign up to set email alerts
|

Uraline, a New Norditerpenoid Alkaloid from Aerial Parts of Delphinium uralense Nevski

Abstract: Uraline, a new norditerpenoid alkaloid, was isolated from aerial parts of Delphinium uralense. The structure of 1alpha,7,8-trihydroxy-6beta,14alpha,16beta-trimethoxy-18-N-(2-methyl)succinylanthranoyloxyaconane was ascribed to the new compound on the basis of 1H and 13C NMR, IR, and mass spectra. The known alkaloids methyllycaconitine and delcorine were also isolated from the plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…They found that the whole plant of D. anthriscifolium contained five C18-diterpenoid alkaloids such as anthriscifoltine A, anthriscifoltine B, deoxydelcorine, anthriscifolcine A, and anthriscifolcine G (50). Aerial parts of D. uralense have been described to have alkaloids methyllycaconitine and delcorine, as well as a norditerpenoid alkaloid, which was called Uraline (51). Using chromatographic techniques and spectroscopic method, to isolate the phytoconstituents and structures of compounds from D. grandiflorum were performed.…”
Section: Traditional Applicationmentioning
confidence: 99%
“…They found that the whole plant of D. anthriscifolium contained five C18-diterpenoid alkaloids such as anthriscifoltine A, anthriscifoltine B, deoxydelcorine, anthriscifolcine A, and anthriscifolcine G (50). Aerial parts of D. uralense have been described to have alkaloids methyllycaconitine and delcorine, as well as a norditerpenoid alkaloid, which was called Uraline (51). Using chromatographic techniques and spectroscopic method, to isolate the phytoconstituents and structures of compounds from D. grandiflorum were performed.…”
Section: Traditional Applicationmentioning
confidence: 99%
“…Furthermore, eleven known diterpenoid alkaloids were determined to be delbruline ( 5 ) [ 11 ], delpheline ( 6 ) [ 13 ], lycoctonine ( 7 ) [ 11 ], delbrunine ( 8 ) [ 11 ], delcosine ( 9 ) [ 11 ], uraphine ( 10 ) [ 14 ], anthranoyllycoctonine ( 11 ) [ 15 ], sharwuphinine A ( 12 ) [ 16 ], browniine ( 13 ) [ 11 ], shawurensine ( 14 ) [ 17 ], and delavaine B ( 15 ) [ 17 ] by comparison of their corresponding spectroscopic data with those reported previously in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…(section Delphinastrum DC) [1]. We reported previously on the isolation from the aerial part of this plant collected during the start of budding in the Southern Urals (Zilair Plateau) of methyllycaconitine, delcorine, and grandiflorine (uraline) [2].In continuation of research on the alkaloid composition of the aerial part of D. uralense, we isolated from the benzene extract of the moderately basic fraction (A, pH 6) [2] by column chromatography and semi-preparative HPLC the known alkaloids dehydrodelcorine, delpheline, deltaline, deltamine, and elasine, and alkaloid 1, which has not previously been described and which we called uraphine. We also isolated deacetylelasine, which was isolated by us for the first time from plant material and has been prepared previously via alkaline hydrolysis of elasine [3].…”
mentioning
confidence: 99%
“…(section Delphinastrum DC) [1]. We reported previously on the isolation from the aerial part of this plant collected during the start of budding in the Southern Urals (Zilair Plateau) of methyllycaconitine, delcorine, and grandiflorine (uraline) [2].…”
mentioning
confidence: 99%